Analysis of Occupational Safety Risk Levels in Mining Activities at PT Golden Great Borneo Lahat Regency, South Sumatra Province - Akbar, Ilham; Fadhilah, Fadhilah; Anarta, Rudy; Saldy, Tri Gamela (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2024)
Mining activities are one of the activities that have high risks at every stage of their operational activities, so every potential hazard and risk that exists must be controlled to prevent accidents from occurring. This research aims to identify, assess, and control hazards and risks at every stage of mining activities at PT Golden Great Borneo. This research uses a semi-quantitative method, where hazard and risk assessment is carried out with a matrix of parameters of likelihood, exposure, and consequence. From the results of the research, the highest occupational safety risk in loading activities is that the distance between units is too close which can result in units crashing/nudging other units, the highest risk in hauling activities is thick dust so that visibility is less than 40 meters, and the highest risk in dumping activities is that the supervisor is in a blind spot area. Kegiatan penambangan merupakan salah satu kegiatan yang memiliki risiko tinggi pada setiap tahapan kegiatan operasional nya, sehingga setiap potensi bahaya dan risiko yang ada harus dikendalikan untuk mencegah terjadi nya kecelakaan. Penelitian ini bertujuan untuk melakukan identifikasi, penilaian, dan pengendalian bahaya dan risiko pada setiap tahapan kegiatan penambangan di PT. Golden Great Borneo. Penelitian ini menggunakan metode semi kuantitatif, dimana penilaian bahaya dan risiko dilakukan dengan matrik parameter tingkat kemungkinan, paparan, dan konsekuensi. Dari hasil penelitian risiko keselamatan kerja tertinggi pada kegiatan loading adalah jarak antar unit terlalu dekat yang dapat mengakibatkan unit menabrak/menyenggol unit lain, risiko tertinggi pada kegiatan hauling debu yang tebal sehingga jarak pandang kurang dari 40 meter, dan risiko tertinggi pada kegiatan dumping adalah pengawas berada pada area blind spot.